Cointegration of Banking Performance on World Oil Prices - Lubis, Jisman M.; ., Moeljadi; Ratnawati, Kusuma; Djazuli, Atim (Journal of Ecohumanism, 2024)
This study investigates the cointegration between banking performance and global oil prices from 2014 to 2021. Using the Augmented Dickey-Fuller (ADF) test for cointegration analysis, the research examines the relationships between global crude oil prices and banking performance indicators such as Return on Assets (ROA), Return on Equity (ROE), Price to Book Value (PBV), and Loan to Deposit Ratio (LDR). The findings reveal significant cointegration between global crude oil prices and the banking performance variables. Notably, an inverse correlation was observed in 2021, indicating a deviation from the established pattern.